PROBLEMATIKA PROSES REHABILITASI & REONSTRUKSI PASCA BENCANA MENGUNAKAN METODE PARTISIPATIF MASYARAKAT - Ira Modifa; Robert Tua Siregar; Rudi Salam Sinaga (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2020)
In the handling of the 2004 Aceh Tsunami Disaster and the 2004 Nias Earthquake, many parties as providers of assistance used a community-based rehabilitation and reconstruction development model one of which is UN-HABITAT under the auspices of the United Nations, This study aims to find the most effective and fair participatory postmortem participatory development guidelines for disaster-affected communities through case studies of Aceh Nias Settlement Support Program (ANSSP) 2005-2007. Analytical descriptive methods are used to obtain data. Data collection techniques used literature study and documentation study. The results of the study found that participatory community-based development, especially post-disaster handling, has proven good results. The literature study, interview and ANSSP report book 2007 published by UN - Habitat, illustrates that the participatory development model is able to answer all negative factors.